2014
DOI: 10.1371/journal.pone.0103736
|View full text |Cite
|
Sign up to set email alerts
|

Improved Efficacy and Reduced Toxicity of Doxorubicin Encapsulated in Sulfatide-Containing Nanoliposome in a Glioma Model

Abstract: As a glycosphingolipid that can bind to several extracellular matrix proteins, sulfatide has the potential to become an effective targeting agent for tumors overexpressing tenasin-C in their microenvironment. To overcome the dose-limiting toxicity of doxorubicin (DOX), a sulfatide-containing nanoliposome (SCN) encapsulation approach was employed to improve treatment efficacy and reduce side effects of free DOX. This study analysed in vitro characteristics of sulfatide-containing nanoliposomal DOX (SCN-DOX) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 61 publications
(81 reference statements)
1
9
0
Order By: Relevance
“…Moreover, this effect was visible at concentrations approximately two- to threefold lower than that of the free drug. This is in agreement with previous studies that demonstrated a remarkable enhancement of the cytotoxic actions of DOX when included in liposomes, nanoparticles or other lipid-based formulations 6670. To enhance the efficacy of DOX for further in vivo studies, we designed two liposomal formulations based on the co-encapsulation of DOX and CUR.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Moreover, this effect was visible at concentrations approximately two- to threefold lower than that of the free drug. This is in agreement with previous studies that demonstrated a remarkable enhancement of the cytotoxic actions of DOX when included in liposomes, nanoparticles or other lipid-based formulations 6670. To enhance the efficacy of DOX for further in vivo studies, we designed two liposomal formulations based on the co-encapsulation of DOX and CUR.…”
Section: Resultssupporting
confidence: 85%
“…This is in agreement with previous studies that demonstrated a remarkable enhancement of the cytotoxic actions of DOX when included in liposomes, nanoparticles or other lipid-based formulations. 66 70 To enhance the efficacy of DOX for further in vivo studies, we designed two liposomal formulations based on the co-encapsulation of DOX and CUR. The composition of these formulations was established using the Optimizer function in Modde 11 Pro software.…”
Section: Resultsmentioning
confidence: 99%
“…The tumor growth inhibition study was initiated at an early stage of tumor growth, to test the therapeutic potential of the liposomes. With the help of literature survey a 2 mg/kg DOX dose was chosen (Gao et al., 2005 ; Biswas et al., 2013 ; Zhao et al., 2013 ; Apte et al., 2014 ; Lin et al., 2014 ; Sriraman et al., 2016 ; Zahmatkeshan et al., 2016 ). Compared to the control and free DOX-treated tumors, all the liposomal DOX groups showed effective control of tumor growth in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover the drug-facilitated toxicity is dependent on the release rate of DOX from the NCs at cellular level. 43 Though the IC 50 value of PEG-Cu 2 S-Fol-DOX is higher than that of free DOX, the favored targeting of cancer cells achieved by PEG-Cu 2 S-Fol-DOX is extremely beneficial for a drug delivery system. The PEG-Cu 2 S-Fol-DOX were found to preferentially accumulate in glioma cells (Figure.…”
mentioning
confidence: 99%